Prescribing Functional Additives for Treating the Poor Performances of High‐Voltage (5 V‐class) LiNi0.5Mn1.5O4/MCMB Li‐Ion Batteries. Issue 9 (4th December 2017) - Xu, Gaojie; Pang, Chunguang; Chen, Bingbing; Ma, Jun; Wang, Xiao; Chai, Jingchao; Wang, Qingfu; An, Weizhong; Zhou, Xinhong; Cui, Guanglei; Chen, Liquan
Abstract: In this paper, tris(trimethylsilyl) phosphite (TMSP) and 1, 3‐propanediolcyclic sulfate (PCS) are unprecedentedly prescribed as binary functional additives for treating the poor performances of high‐voltage (5 V‐class) LiNi0.5 Mn1.5 O4 /MCMB (graphitic mesocarbon microbeads) Li‐ion batteries at both room temperature and 50 °C. The high‐voltage LiNi0.5 Mn1.5 O4 /MCMB cell with binary functional additives shows a preponderant discharge capacity retention of 79.5% after 500 cycles at 0.5 C rate at room temperature. By increasing the current intensity from 0.2 to 5 C rate, the discharge capacity retention of the high‐voltage cell with binary functional additives is ≈90%, while the counterpart is only ≈55%. By characterizations, it is rationally demonstrated that the binary functional additives decompose and participate in the modification of solid–electrolyte interface layers (both electrodes), which are more conductive, protective, and resistant to electrolyte oxidative/reductive decompositions (accompanying active‐Li + consuming parasitic reactions) due to synergistic effects. Specifically, the TMSP additive can stabilize LiPF6 salt and scavenge erosive hydrofluoric acid. More encouragingly, at 50 °C, the high‐voltage cell with binary functional additives holds an ultrahigh discharge capacity retention of 79.5% after 200 cycles at 1 C rate. Moreover, a third designed self‐extinguishing flame‐retardant additive of (ethoxy)‐penta‐fluoro‐cyclo‐triphosphazene (PFPN) is introduced for reducing the flammability of the aforementioned binary functional additives containing electrolyte. Abstract : Here, the Chinese idiom "Xuan Hu Ji Shi" (Practise medicine in order to help the people) is used to express the willingness to save the earth home in peril by developing high energy/high power renewable‐energy storage systems. Specifically, several functional additives are prescribed for electrolyte to greatly enhance the performances of a promising high‐voltage (5 V‐class) LiNi0.5 Mn1.5 O4 /graphite battery system.